![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
(5x - 2y)(x2 - xy + 1)
= 5x3 - 5x2y + 5x - 2x2y + 2xy2 - 2y
= 5x3 - 7x2y + 2xy2 + 5x - 2y
(x - 1)(x + 1)(x + 2)
= (x2 - 1)(x + 2)
= x3 + 2x2 - x - 2
1/2x2y2(2x + y)(2x - y)
= 1/2x2y2(4x2 - y2)
= 2x4y2 - 1/2x2y4
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 2:
\(\left(5x+1\right)^2-\left(2xy-3\right)^2\)
\(=25x^2+10x+1-\left(2xy-3\right)^2\)
\(=25x^2+10x+1\left(4x^2y^2-12xy+9\right)\)
\(=25x^2+10x+1-4x^2y^2+12xy-9\)
\(=25x^2-4x^2y^2+10x+12xy-8\)
Bài 2:
\(\left(x-1\right)\left(x^2+x+1\right)=x^2\left(x-9\right)+2x+6\)
\(=x^3-1=x^3-9x^2+2x+6\)
\(=x^3-9x^2+2x+6=x^3-1\)
\(=x^3-9x^2+2x+6+1=x^3-1+1\)
\(=x^3-9x^2+2x+7=x^3\)
\(=x^3-9x^2+2x+7-x^3=x^3-x^3\)
\(=-9x^2+2x+7=0\)
\(\Rightarrow x=-\frac{7}{9};x=1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,=-15x^3+10x^4+20x^2\\ b,=2x^3+2x^2+4x-x^2-x-2=2x^3+x^2+3x-2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
\(3a.\left(2a^2-ab\right)=6a^3-3a^2b\)
\(\left(4-7b^2\right).\left(2a+5b\right)=8a+20b-14ab^2-35b^3\)
Bài 2:
\(2x^2-6x+xy-3y=2x.\left(x-3\right)+y.\left(x-3\right)=\left(x-3\right).\left(2x+y\right)\)
Bài 3: Tại x = 3/2, y =1/3 thì Q = 67/9
Bài 4:
\(\left(\frac{1}{x+1}+\frac{2x}{1-x^2}\right).\left(\frac{1}{x-1}\right)\) \(\frac{1}{\left(x+1\right).\left(x-1\right)}+\frac{2x}{\left(1-x^2\right).\left(x-1\right)}=\frac{x-1}{\left(x+1\right).\left(x-1\right)^2}+\frac{-2x}{\left(x-1\right)^2.\left(x+1\right)}\)
= \(\frac{x-1-2x}{\left(x+1\right).\left(x-1\right)^2}=\frac{-\left(x+1\right)}{\left(x+1\right).\left(x-1\right)^2}=\frac{-1}{\left(x-1\right)^2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{3\left(x-2\right)}{4}\div\frac{2-x}{2}=\frac{3\left(x-2\right)}{4}\times\frac{-2}{x-2}=\frac{-3}{2}\)
học tốt
Rút gọn nhé !
\(\frac{3}{4}.\left(x-2\right):\frac{1}{2}.\left(2-x\right)=\frac{3x-6}{4}.2.\left(2-x\right)\)
\(=\frac{3x-6}{4}.\left(4-2x\right)=\frac{\left(3x-6\right).\left(4-2x\right)}{4}\)
\(=\frac{\left(12x-24\right)-\left(6x^2+12x\right)}{4}=\frac{-24-6x^2}{4}\)
\(=\frac{-12-3x^2}{2}=\frac{-3.\left(4+x^2\right)}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Giải:
4xn (7xn-1 + x - 5) - 2xn-2 (14xn+1 - 10x2)
= 28x2n-1 +4xn + 1 – 20xn - 28x2n-1 + 20xn
= 4xn+1
a) (x-1)(x+1)(x+2)
=\(\left(x^2-1\right)\) (x+2)
= \(x^3+2x^2-x-2\)
TL:
a) (x-1) (x+2)
\(=\left(x^2-1\right)\)(x+2)
\(=x^3\)\(+2x^2\)\(-x-2\)